Amido fermentado de alpiste (Phalariscanariensis L.) enriquecido com microcápsulas contendo compostos polifenólicos de casca e semente de jabuticaba (Myrciaria cauliflora) - Batista, Rayssa Dias (2019)
Canaryseed, alsoknown as annualcanarygrass, canarygrass anual, canário grama, alpista, capim alpista and milho alpista, stands out as a new sourceofstarch, composedofapproximately 60% ofthiscarbohydrate. The characteristicsofthiscropmake it a favorable cereal for foodand industrial applications. Fermentationis a processusedtomodifystarchstructuresandiswidelyused for thepreparationofcheesebreadand biscuits. The additionofpolyphenolsfrom jabuticaba wouldenrichtheseproducts, however it issusceptibletooxidationbyexternalelementssuch as heat, light andstorage time. In this case, emergingmicroencapsulationtechniquesallowto improve thestabilityofthesecompounds. The presentstudyaimedto prepare biscuits fromfermentedcanaryseedstarch (Phalariscanariensis L.) andtoenrichwithmicrocapsulesofpolyphenoliccompoundsoftheseedsand peles jabuticaba (Myrciaria cauliflora) mixture. The microcapsuleswereobtainedbythe experimental design DCCR (central rotationalcompound design) varyingtheinitialamountofsodiumalginateand volume ofthehydroalcoholicseedsand peles jabuticaba. A total of 11 treatmentswereobtainedwiththehighestcontentofmicroencapsulatedphenoliccompoundfound in treatments 2, 8 and4, andtheextract volume variableshowedgreaterinfluenceonthe response ofthephenoliccompoundcontentandencapsulationefficiency. The fermentationofthestarchoccurredduring 45 daysof natural fermentationwithsubsequentdrying in thesun. The resultsofthemicrobiologicalanalyzeswerewithinthelimitsestablishedbylegislation, withanincrease in theamylosecontentandlowerviscosityand retrograde degradationthanthenativecanaryseedstarch. Fermentedcanaryseedstarchdidnot show expansioncapacityandafteradditionofthemicrocapsules in the biscuits, treatments2and 3 presentedhighercontentofphenoliccompounds.